Characterization of Nutmeg Mace Extract (Myristica fragrans Houtt.) Obtained Using Green Solvents and Its Antioxidant and Antifungal Potential - Wicaksono, Dani Satrio; Nurdyansyah, Fafa; Affandi, Arief Rakhman (Department of Food Science and Biotechnology, Faculty of Agroindustrial and Biosystem Technology, Universitas Brawijaya, 2026)
Food contamination by Aspergillus flavus is a serious concern because this fungus can produce toxic aflatoxins. Nutmeg mace (Myristica fragrans Houtt.) contains bioactive compounds with potential antifungal properties. This study investigated the effects of three green solvents—glycerol (VG), propylene glycol (PG), and polyethylene glycol 400 (PEG-400)—and two extraction methods, maceration and infusion, on phytochemical content, antioxidant activity, and antifungal activity against A. flavus. PEG-400 extracts showed the strongest antifungal activity, with inhibition zones of 15.41–19.84 mm, moderate antioxidant activity, and consistently strong phytochemical responses. PG produced the highest DPPH radical-scavenging activity (63.09%) and moderate antifungal effects. VG showed the weakest antioxidant and antifungal activities. Infusion generally produced greater biological activity than maceration. These results confirm that solvent type and extraction method significantly influence extract performance and support green extraction approaches for developing functional, environmentally friendly natural antifungal products.